Evaluation of Meal Carbohydrate Counting Errors in Patients with Type 1 Diabetes - Buck, Sina; Krauss, Collin; Waldenmaier, Delia; Liebing, Christina; Jendrike, Nina; Högel, Josef; Pfeiffer, Boris M.; Haug, Cornelia; Freckmann, Guido (Experimental and Clinical Endocrinology & Diabetes, 2021)
Aim Correct estimation of meal carbohydrate content is a prerequisite for successful intensified insulin therapy in patients with diabetes. In this survey, the counting error in adult patients with type 1 diabetes was investigated.Methods Seventy-four patients with type 1 diabetes estimated the carbohydrate content of 24 standardized test meals. The test meals were categorized into 1 of 3 groups with different carbohydrate content: low, medium, and high. Estimation results were compared with the meals’ actual carbohydrate content as determined by calculation based on weighing. A subgroup of the participants estimated the test meals for a second (n=35) and a third time (n=22) with a mean period of 11 months between the estimations.Results During the first estimation, the carbohydrate content was underestimated by −28% (−50, 0) of the actual carbohydrate content. Particularly meals with high mean carbohydrate content were underestimated by −34% (−56, −13). Median counting error improved significantly when estimations were performed for a second time (p<0.001).Conclusions Participants generally underestimated the carbohydrate content of the test meals, especially in meals with higher carbohydrate content. Repetition of estimation resulted in significant improvements in estimation accuracy and is important for the maintenance of correct carbohydrate estimations. The ability to estimate the carbohydrate content of a meal should be checked and trained regularly in patients with diabetes.
Keywords: diabetes; carbohydrate counting; estimation accuracy